Gaya Hidup dan Dukungan Suami dalam Pengambilan Keputusan Pertolongan Persalinan Di Kabupaten Bantul - Istri Bartini; Isabella Rahmawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Contributing factors in how women capable to make a decision about delivery care are attitude and income factor that will shape their lifestyle, also husband support. People who have in both consumptive and simple lifestyle assumed that giving birth with obstetrician is more save rather than midwife. This research is kualitatif and crossectional study, using stratified random sampling to figure out correlation between life style and husband support with women decision in their delivery care. Questionnaire have distributed to 140 women who giving birth at private practice, public health center, clinic and hospital. This study reveals that most of women (60,7%) have a simple lifestyle while 39,3% categories as consumptive lifestyle. There no significant correlation, refer to p-value of lifestyle is 0.226 and p-value of husband support is 0.648. Woman who have good support from her husband tend to have a sense of coherence, in which influence on their attitude during pregnant and delivery. Inconclusion, most women have a simple lifestyle, but there is no significant correlation in it. Most women have good support from their husband, however there is no significant correlation to make a decision in their delivery care.Keywords: lifestyle, husband support, sense of coherence